Links between Soil Fungal Diversity and Plant and Soil Properties on the Loess Plateau - Yang, Yang; Dou, Yanxing; Huang, Yimei; An, Shaoshan (Frontiers in Microbiology, 2017)
Previous studies have revealed inconsistent correlations between fungal diversity and plant/soil properties from local to global scales. Here, we investigated the internal relationships between soil fungal diversity and plant/soil properties on the Loess Plateau following vegetation restoration, using Illumina sequencing of the internal transcribed spacer 2 (ITS2) region for fungal identification. We found significant effects of land use types (Artificial forest, Af; Natural shrub, Ns; Artificial grassland, Ag; Natural grassland, Ng; slope cropland, Sc) on soil fungal communities composition, and the dominant phyla were Ascomycota, Basidiomycota, and Zygomycota, which transitioned from Basidiomycota-dominant to Ascomycota-dominant community due to vegetation restoration. The Chao1 richness, Shannon's diversity and ACE indices were significantly influenced by land use types with the order of Ns > Af > Ng > Ag > Sc, and the total number of OTUs varied widely. In contrast, Good's coverage and Simpson's diversity indicated no significant difference among land use types (p > 0.05). Correlation analysis showed that plant and soil properties were closely related to fungal diversity regardless of land use types. In addition, soil organic carbon (SOC) and Hplant (plant richness, Shannon-Wiener index) were strong driving factors that explained fungal diversity. As revealed by the structural equation model (SEM) and generalized additive models (GAMs), fungal diversity was directly and indirectly affected by soil and plant properties, respectively, providing evidence for strong links between soil fungal diversity and plant and soil properties on the Loess Plateau.